2022
DOI: 10.1108/jrim-10-2021-0268
|View full text |Cite
|
Sign up to set email alerts
|

The virality of advertising content

Abstract: PurposeThe study aims to examine “Advertisement content likeability” and its relationships with consumers' purchase and sharing intentions.Design/methodology/approachSecond-order factor analysis was applied. Structural equation modeling (SEM) was used to measure the moderating effects of technology adoption model, knowledge sharing and Internet maven traits on advertising content's virality.FindingsResults indicate the dimensional structure of ad content likeability that is relevant in predicting consumers' sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 118 publications
0
1
0
Order By: Relevance
“…In fact, due to the high informational content of such posts, many multi-brand posts by influencers are shared by their followers with their friends and acquaintances who they think may benefit from the knowledge. This is in line with the study of Kaur, Paul & Sharma (Kaur et al, 2022) whose results showed that informational appeal of an ad increased content likeability and sharing of such ads.…”
Section: (Table 1)supporting
confidence: 91%
“…In fact, due to the high informational content of such posts, many multi-brand posts by influencers are shared by their followers with their friends and acquaintances who they think may benefit from the knowledge. This is in line with the study of Kaur, Paul & Sharma (Kaur et al, 2022) whose results showed that informational appeal of an ad increased content likeability and sharing of such ads.…”
Section: (Table 1)supporting
confidence: 91%
“…Moreover, Rath et al (2017) contended that if consumers like the ad, they tend to try the product. Additionally, Kaur et al (2023) have stated that ad likability is a significant predictor of consumers' purchase intentions.…”
Section: Review Of Literaturementioning
confidence: 99%